Formulation and Evaluation of Pulsatile Drug Delivery System of Zafirlukast - Madhavi, Ala Vijaya; Brahma Reddy, D Rama; Venugopal, M; Srihari, N; Chenniah, P; Koteswarao, P (Journal of Drug Delivery and Therapeutics, 2020)
In the current scenario of pharmaceutical research much attention has been focused on patients health in terms of therapeutic efficacy and economical standards (price factor).The formulation design consist of core tablets designed by direct compression method. Core tablets were coated with an naturally occurring swelling agent (carbopol & Karaya gum). Evaluation studies were performed for prepared pulsatile tablets hardness. In in vitro release profile of 6 hours study in first 5 hours it shows minimum drug release and at the end of six hours rapid and transient release was observed. Stability studies proved that coating of tablets seems to decrease the effect of temperature and moisture on degradation of Zafirlukast. The pulsatile release has been achieved from tablet over a 7-8 hour period.